Medial Parietal Cortex Activation Related to Attention Control Involving Alcohol Cues - Gladwin, Thomas E.; ter Mors – Schulte, Mieke H.; Ridderinkhof, K Richard; Wiers, Reinout W. (Frontiers in Psychiatry, 2013)
Attention plays a central role in theories of alcohol dependence; however, its precise role in alcohol-related biases is not yet clear. In the current study, social drinkers performed a spatial cueing task designed to evoke conflict between automatic processes due to incentive salience and control exerted to follow task-related goals. Such conflict is a potentially important task feature from the perspective of dual-process models of addiction. Subjects received instructions either to direct their attention towards pictures of alcoholic beverages, and away from non-alcohol beverages; or to direct their attention towards pictures of non-alcoholic beverages, and away from alcohol beverages. A probe stimulus was likely to appear at the attended location, so that both spatial and non-spatial interference was possible. Activation in medial parietal cortex was found during “Approach Alcohol” versus “Avoid Alcohol” blocks. This region is associated with the, possibly automatic, shifting of attention between stimulus features, suggesting that subjects may have shifted attention away from certain features of alcoholic cues when attention had to be directed towards an upcoming stimulus at their location. Further, activation in voxels close to this region was negatively correlated with riskier drinking behavior. A tentative interpretation of the results is that risky drinking may be associated with a reduced tendency to shift attention away from potentially distracting task-irrelevant alcohol cues. The results suggest novel hypotheses and directions for future study, in particular towards the potential therapeutic use of training the ability to shifting attention away from alcohol-related stimulus features.